2015
DOI: 10.1007/s40519-015-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviours in adolescent girls: the role of body shame and body dissatisfaction

Abstract: This study provides further evidence of the experience of body shame among adolescent girls and suggests that this shame is associated with disordered eating behaviours. Future longitudinal research designed to specifically explore body shame and other potentially shared risk factors is needed, and would enhance our understanding of eating disorder aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
1
37
0
3
Order By: Relevance
“…Notwithstanding the consideration of shame as an adaptive emotion, high levels of shame are associated with severe social difficulties, and have been consistently linked to the development and maintenance of different mental health conditions [11,12], specifically depression [e.g., 4,13,26] and eating psychopathology [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notwithstanding the consideration of shame as an adaptive emotion, high levels of shame are associated with severe social difficulties, and have been consistently linked to the development and maintenance of different mental health conditions [11,12], specifically depression [e.g., 4,13,26] and eating psychopathology [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding eating psychopathology, shame has been regarded as a central feature [16,19,20]. In fact, several studies have shown that eating disorders' patients, when compared to nonclinical groups, report higher levels of shame even after treatment [16,19,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents-girls are seriously troubled and unsatisfied with their boy shapes. It is a potential mediator in changing their eating behavior [30]. Especially dangerous is influence of food commercials in primary school on children's consuming habits [24].…”
mentioning
confidence: 99%